2013
DOI: 10.1007/s11136-012-0338-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mental disorders in tinnitus patients performed with Composite International Diagnostic Interview

Abstract: In the present study, we have detected a high rate (almost half of the cases) of psychological disorders occurring in patients with chronic tinnitus. The patients diagnosed with psychological disorders were predominantly affected by affective and anxiety disorders. Psychological disorders were associated with severity of tinnitus distress. Our findings imply a need for routine comprehensive screening of mental disorders in patients with chronic tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 49 publications
1
29
0
8
Order By: Relevance
“…In the chronic pain literature, research suggests that attention factors selectively modulate the awareness of pain, while mood selectively modulates the unpleasantness of the pain (Bushnell et al, 2013). Impaired cognitive control has also been implicated in anxiety (Derryberry and Reed, 2002) and depression (Fales et al, 2008), with both psychological conditions having a high incidence rate in CT populations (Zirke et al, 2013). As such, we propose that the ongoing awareness and severity of CT is underpinned by a failure of top–down cognitive resources, specifically cognitive and emotional control, resulting in a reduced ability to switch attention away from the tinnitus sound.…”
Section: Discussionmentioning
confidence: 99%
“…In the chronic pain literature, research suggests that attention factors selectively modulate the awareness of pain, while mood selectively modulates the unpleasantness of the pain (Bushnell et al, 2013). Impaired cognitive control has also been implicated in anxiety (Derryberry and Reed, 2002) and depression (Fales et al, 2008), with both psychological conditions having a high incidence rate in CT populations (Zirke et al, 2013). As such, we propose that the ongoing awareness and severity of CT is underpinned by a failure of top–down cognitive resources, specifically cognitive and emotional control, resulting in a reduced ability to switch attention away from the tinnitus sound.…”
Section: Discussionmentioning
confidence: 99%
“…Despite heavy auditory impairment of the target group, there were no differences between GAD‐7 scores pre‐ and post‐CI implantation, indicating affective stability of the patients our study sample. Zirke et al report high GAD‐7 scores in patients with chronic tinnitus and auditory disorders. Likewise, Andersson et al reported a link between psychopathological comorbidities in patients with auditory handicaps.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-three percent of patients who suffered from tinnitus reported psychiatric symptoms. Mental disorders, including depression, dysthymia, insomnia, loss of concentration, somatoform disorders, anxiety, and obsessive compulsive disorder have been reported to occur in up to 46% of patients 28. Some groups29 have found an important relationship between mental health and tinnitus or sensitivity to noise.…”
Section: Discussionmentioning
confidence: 99%